Measurement of floor vibrations using a heel drop test - Blakeborough, A; Williams, M (2003)
As floor vibration problems increase, there is a need for simple and reliable methods of determining a floor's dynamic properties. This paper presents a technique called the instrumented heel drop test, in which the floor is excited by a series of heel drops performed on top of a slim load cell placed on the floor. The test is shown to give excellent resolution of natural frequencies in the range 2 - 15 Hz, which corresponds well with the frequency range of interest in floor vibration problems. The method appears to offer some advantages over the well-established technique of instrumented hammer testing, in terms of the quality of frequency resolution and the speed of the test.